2020
DOI: 10.1002/fuce.201900131
|View full text |Cite
|
Sign up to set email alerts
|

Development of 1 kW‐class Ammonia‐fueled Solid Oxide Fuel Cell Stack

Abstract: Power generation performance and long‐term durability of ammonia‐fueled solid oxide fuel cell (SOFC) systems are investigated with SOFC stacks consisting of 30 planar anode‐supported cells. SOFC systems with three different operation modes are employed: direct ammonia, external decomposition and autothermal decomposition. A novel BaO/Ni/Sm2O3/MgO catalyst is newly developed for the external ammonia cracker, whereas a Co‐Ce‐Zr composite oxide catalyst is used for the autothermal ammonia cracker. Initial perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 34 publications
3
32
0
7
Order By: Relevance
“…For natural gas or methane fueled SOFC, η P usually ranges from 42 to 64% [65][66][67] depending on temperature, pressure, current density, reactant utilization, anode off-gas recycling, and balance of plant (BOP) components. For ammonia, η P varies between 40 to 60% as is widely reported [68][69][70]. For our processes, η RTE (Figure 6C) as calculated from Equation 11, follows the order hydrogen (62.1%) > methane by Route 1 (43.4%) > ammonia by Route 2 (41.1%) > methane by Route 2 (40.4%) > ammonia by Route 1 (39.2%).…”
Section: Resultssupporting
confidence: 71%
“…For natural gas or methane fueled SOFC, η P usually ranges from 42 to 64% [65][66][67] depending on temperature, pressure, current density, reactant utilization, anode off-gas recycling, and balance of plant (BOP) components. For ammonia, η P varies between 40 to 60% as is widely reported [68][69][70]. For our processes, η RTE (Figure 6C) as calculated from Equation 11, follows the order hydrogen (62.1%) > methane by Route 1 (43.4%) > ammonia by Route 2 (41.1%) > methane by Route 2 (40.4%) > ammonia by Route 1 (39.2%).…”
Section: Resultssupporting
confidence: 71%
“…41,3 Power generation on a large scale has already been introduced by Kishimoto et al, who demonstrated an ammonia-fed SOFC stack consisting of 30 planar anode supported cells and achieved a 1kW power output with 52 % direct current electrical efficiency. 242…”
Section: Perspective and Challenges Of Ammonia-fed Sofcsmentioning
confidence: 99%
“…In the existing literature there has been great attention on potential catalysts for the ammonia oxidation [62][63][64][65] and specifically for SOFCs [66,67]. The performance of ammonia fuel cell for land-based energy production or for other systems has attracted attention in the literature, as presented in Table 3.…”
Section: Ammonia Fuel Cellsmentioning
confidence: 99%